First report of a B chromosome in a natural population of Astyanax altiparanae (Characiformes, Characidae) - Hashimoto, Diogo Teruo [UNESP]; Gonçalves, Vanessa Regina [UNESP]; Bortolozzi, Jehud [UNESP]; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (Sociedade Brasileira de Genética, 2008)
Several species of the genus Astyanax have already been genetically studied, and B-chromosomes have been considered to be an interesting feature in some species of this group. In the present paper we report, for the first time, the occurrence of a B microchromosome in a natural population of A. altiparanae. This additional genomic element was identified as an acrocentric chromosome, similar in size to the smallest chromosomal pairs of the standard karyotype. Analysis of the constitutive heterochromatin pattern by C-banding evidenced heterochromatic blocks located on centromeric, pericentromeric, and interstitial regions of some chromosomes, and also positive marks in a subtelocentric chromosomal pair that presented the short arms entirely heterochromatic. The application of this methodology also revealed a heterochromatic pattern in the extra chromosome, a typical feature of supernumerary chromosomes.
Keywords: B chromosomes; fish cytogenetics; Astyanax altiparanae